Caracterización de la biomasa residual de dos ecotipos de (Lupinus mutabilis Sweet) en el campus experimental ceasa, en el periodo 2020-2021. - Centeno Bernal, Martha Genoveva (2021)
In Ecuador, legumes are part of the production system, mainly in the Sierra region. The lupine is one of them since its seed is used as food. It presents heterogeneity between the production units being necessary its analysis in order to characterize the biomass of two ecotypes in their four harvest indices in a physical and chemical form, generating a circular agriculture, environmentally friendly. The research was developed in “San Miguelito de Pillaro” neighborhood, a randomized complete block design (RCBD) was applied, with three replications and two factors under study, Factor A, considered as genetic material consisting of two promising lines: Local Peruvian Ecotype, and Local Ecotype or Cotopaxi, and Factor B, composed of 4 Harvest Indices called soft grain index, lime green index, yellow index and brown index. The averages obtained as result from the physical-chemical characterization of the Cotopaxi ecotype were 1.54 m in height, 383.64 gr in fresh weight, 94.85 gr in dry weight, 65.89 in humidity, 4.65% w / w in alkaloids, 19 nodules per plant, 30.05% in fiber, 14.45% in protein regarding the local Peruvian ecotype, the following averages were obtained 1.48m in height, 261.09gr in fresh weight, 82.56gr in dry weight, 68.87% in humidity, 17 nodules per plant, 3.96% p / p in alkaloids, 29.68% fiber and 13.92 in protein, thus determining that the factors under study do not present a significant difference in the analyzed characteristics and can be used as green manure producing benefits such as nutrient recycling, closed energy flows , balanced pest populations, soil fertility performance.